2012
DOI: 10.1111/j.1442-200x.2012.03622_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese guidelines for the management of intussusception in children, 2011

Abstract: Background: The Japanese Society of Emergency Pediatrics has formulated evidence-based guidelines for the management of intussusception in children in order to diagnose intussusceptions promptly, to initiate appropriate treatment as early as possible, and to protect intussuscepted children from death. Methods: Literature was collected systematically via the Internet using the key words "intussusception" and "children."The evidence level of each paper was rated in accordance with the levels of evidence of the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
4
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 124 publications
(230 reference statements)
1
71
4
7
Order By: Relevance
“…Postreduction perforation rates have been previously reported to be low, ranging between 0.14 and 0.75% 4,10,18 with most appreciated during, or immediately after, the reduction.…”
Section: Discussionmentioning
confidence: 96%
“…Postreduction perforation rates have been previously reported to be low, ranging between 0.14 and 0.75% 4,10,18 with most appreciated during, or immediately after, the reduction.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, hospital charts are not necessarily designed for epidemiological investigations. Of 192 cases of intussusception diagnosed by local doctors, 5 were excluded because these cases did not meet with the case definition employed in this study (that of the Japanese Society of Emergency Pediatrics [8]). In at least one case, however, there was a very detailed description of the patient that strongly suggested the presence of intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection form was used to collect information on demography, clinical signs, ultrasound findings, radiological findings, method of treatment, medical history and treatment outcome. Based on the information collected from hospital charts, each case was ascertained according to the definitive diagnosis defined by the Japanese Society of Emergency Pediatrics [8]. Patients coded under K56.1 and matched with the definitive diagnosis of the Japanese Society of Emergency Pediatrics, less than 5 years of age and living in Nha Trang city were included in the final analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the subjects in this study were male. A Japanese guideline for pediatric intussusception, stated that the ratio of 12 male-to-female was 2:1 , and three other wide-scale epidemiologic studies reported male-to-female ratio 1.6:1 to 4,6,10 2.1:1 . Though the numbers of ratio were different, those studies indicated that predominance of male patients in 21 pediatric intussusception .…”
Section: Tabel 1 Distribution Of Subjects' Characteristics Table 2 mentioning
confidence: 99%